Solid Earth and local sea-level change effects on grounding-line stability of the Antarctic ice sheet - Coulon, Violaine; Pattyn, Frank (2019)
Both isostatic effects of ice sheet volume changes and gravitationally-consistent local sea-level variations areknown to have a large impact on timing and magnitude of retreating and advancing ice through grounding-linemigration on glacial-interglacial time scales.Full self-gravitating viscoelastic solid-Earth models (SGVEM) incorporate gravitational, rotational and bedrockdeformational responses to ice-ocean mass redistribution and are thus able to solve the sea-level equation. Onthe other side of the spectrum are ELRA models (Elastic Lithosphere-Relaxed Asthenosphere), often used inconjunction with ice-sheet models. They consider an elastic lithosphere, defined by a given effective lithospherethickness and a relaxation equation for asthenospheric response with a characteristic response time as a function ofasthenosphere viscosity. However, several recent studies suggest strong lateral variations in lithospheric thicknessand asthenosphere viscosity between Eastern and Western Antarctica. More specifically, effective lithospherethickness and mantle viscosity variability in Antarctica induce large spatial variations - across several orders ofmagnitude - of both the flexural rigidity and the asthenospheric response time, with weaker Earth structure thanpreviously thought in Western Antarctica. It has been shown that the combination of bedrock uplift and localsea-level lowering associated with grounding-line retreat reduces Antarctic ice sheet (AIS) mass loss, with greaterstabilization occurring for weaker solid Earth (Gomez et al. 2015, Konrad et al. 2015). Properly approximatingthe interactions of the ice sheet with the solid Earth and local sea-level response is thus key to understand thestability and evolution of the AIS.Here, we develop a simplified Earth model based on the ELRA model that approximates the lateral variationsof the Antarctic Earth structure, leading to spatially varying asthenospheric response time and effectivelithosphere thickness. This is further combined with a gravitationally consistent ...